Hubungan Faktor Lingkungan Fisik Rumah dengan Kejadian Pneumonia di Wilayah Kerja Puskesmas Jatibarang Kabupaten Indramayu - Kholilah Samosir; Eustasia Eustasia (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2019)
Pneumonia is one of the largest contributors to health problems and causes of death of children under five years old. Jatibarang health centre is one of the health centers in the Indramayu regency with the incidence of pneumonia at most each year. According to data from the clinic there were 907 cases of pneumonia in infants aged 1-4 years. Data in 2013 as many as 737 cases. The study aims to analyze the relationship between physical environmental factors and family practice with the incidence of pneumonia in children under five years old in Puskesmas Jatibarang Indramayu regency. This study is a retrospective case-control study method. As the case group and the control group 71 respondents. Analysis of data using univariate, bivariate, and mulivariate analyzes. The results were obtained from 11 variables examined, the variables associated with the incidence of pneumonia is the lighting in the room (p = 0.030 OR 6.080 95% CI 1.193 - 30.978), the lighting in the family room (p = 0.030 OR 10.669 95% CI 1.254 - 90.728) and open the window every day (p = 0.016 OR 2.709 95% CI 1.200 - 6.116). It can be concluded there is a relationship between the lighting in the room, the lighting in the living room with the incidence of pneumonia. Keywords : Pneumonia, children under five years old, physical environment factor, Indramayu